The Analysis of the Influence of Green Supply Chain Management and Low-Cost Strategies on Environmental Performance - Shafira Alya Endyanti; Titik Kusmantini; Tri Wahyuningsih (International Journal of Applied Business and International Management, 2021)
This study aims to analyze the effect of green supply chain management and low-cost strategies on environmental performance. This study used a descriptive quantitative methodology. It surveyed 78 KWTs (Women's Farmers Group) in Sewon Regency, Bantul. The sampling technique was simple random sampling. The results indicate that green supply chain management has a positive effect on environmental performance, and the low-cost strategy has a positive effect on environmental performance.